Knowledge and Attitude of Corporate Social Responsibility by Selected Small Businesses in Ado-Ekiti, Nigeria - Ayobami, Ayodele, Olubayode; Alex, Adedapo, Adeolu; Olanireti, Ayodele, Margaret (American Journal of Social Sciences and Humanities, 2019)
Corporate Social Responsibility over the years is keenly observed as germane to business long term survival. The impact of CSR reflect both in the business performance and societal impact. In Nigeria, it is observed that CSR is mostly practiced by large businesses when compared to small businesses. This study objectives includes accessing the knowledge of small businesses of CSR, know the attitude of small businesses towards CSR and contributing factors to the attitude of small businesses. The researchers used descriptive analysis methods to analyse responses from respondents. Result from the study revealed that majority of respondents were of the view that CSR was strictly for large firms, so small businesses has no business engaging in CSR activities. Most small business considered CSR as waste of scarce resources and irrelevant to business growth. The result also showed that lack of knowledge, less funds, lack of exposure towards CSR and government policy are responsible for poor attitude towards CSR activities. The study recommends that government, pressure groups and other stakeholders should regularly organise programmes through various channels on the need for small businesses to change their perception about CSR. Also association, and government agencies should sanitize small businesses on the importance of CSR to their business and society.